2017
DOI: 10.1080/21541264.2017.1338176
|View full text |Cite
|
Sign up to set email alerts
|

The RNA polymerase II CTD “orphan” residues: Emerging insights into the functions of Tyr-1, Thr-4, and Ser-7

Abstract: The C-terminal domain (CTD) of the RNA polymerase II largest subunit consists of a unique repeated heptad sequence of the consensus Tyr1-Ser2-Pro3-Thr4-Ser5-Pro6-Ser7. An important function of the CTD is to couple transcription with RNA processing reactions that occur during the initiation, elongation, and termination phases of transcription. During this transcription cycle, the CTD is subject to extensive modification, primarily phosphorylation, on its non-proline residues. Reversible phosphorylation of Ser2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…Although substitution of non-tyrosine residues at the Tyr1 position is relatively rare in nature and does not occur in human cells, Tyr1 phosphorylation is conserved from yeast to humans and plays a key role in transcriptional events (Chapman et al, 2008; Yurko and Manley, 2018). Since the molecular mechanism explaining its diverse biological functions remains elusive, the sensitivity of CTD kinases to the chemical properties of Tyr1 side-chain motivated us to investigate if Tyr1 phosphorylation impacts subsequent phosphorylation events by reconstructing sequential CTD phosphorylation in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Although substitution of non-tyrosine residues at the Tyr1 position is relatively rare in nature and does not occur in human cells, Tyr1 phosphorylation is conserved from yeast to humans and plays a key role in transcriptional events (Chapman et al, 2008; Yurko and Manley, 2018). Since the molecular mechanism explaining its diverse biological functions remains elusive, the sensitivity of CTD kinases to the chemical properties of Tyr1 side-chain motivated us to investigate if Tyr1 phosphorylation impacts subsequent phosphorylation events by reconstructing sequential CTD phosphorylation in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…The heptad repeats within the CTD are extensively and dynamically post-translationally modified at different times during the transcription cycle. Of the seven consensus CTD residues, five can be phosphorylated (Y1, S2, T4, S5, and S7), and the two remaining proline residues can undergo isomerization to cis or trans conformations (Heidemann et al, 2013;Yurko and Manley, 2018). Serine-5 phosphorylation (S5p) and serine-2 phosphorylation (S2p) are the most thoroughly studied CTD modifications (Jasnovidova and Stefl, 2013;Buratowski, 2009;Harlen and Churchman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that Pin1 can increase Ssu72′s phosphatase activity for Ser7P and Ser5P [ 44 ]. As mentioned above, the CTD of the largest subunit of RNAPII contains a unique repeated heptad sequence of the consensus Tyr1–Ser2–Pro3–Thr4–Ser5–Pro6–Ser7 [ 45 ]. This phosphorylation profile comprises an informational code coordinating transcription and RNA processing.…”
Section: Mechanism By Which Ssu72 Phosphatase Regulates Gene Exprementioning
confidence: 99%